Attitudes towards English Diversity of Students in the International College and the Non-IC Programmes at a University in Taiwan. (August 2019) - Wang, Chaochang
As English is a lingua franca that has developed along many different pathways with the result that numerous varieties continue to evolve, effective communication requires mutual adjustment and understanding. A considerable body of research on English diversity is focussed on attitudes towards the sociolinguistic reality of English and interactional features in lingua franca contexts. However, very little research has been conducted on the attitudes towards English diversity of students in international education (IE) settings in which adjustment and acceptance are important to communication at all levels. Indeed no research has been done on comparing attitudes of IE settings' local students and those of non-IE students. The purpose of this study is to address this gap in the literature. In this study the participants comprised international students and local Taiwanese students at a university where an international environment has been created via an international college offering degree programmes with English used as the instructional medium and the intercultural means of communication. The study results shed light on how international education of this nature may impact the views of and attitudes towards the sociolinguistic reality of English today.